An Ecocultural Perspective on Eating-Related Routines Among Low-Income Families With Preschool-Aged Children. (July 2019) - Bekelman, Traci A.; Bellows, Laura L.; Clark, Lauren; Thompson, Darcy A.; Kemper, Geri; McCloskey, Morgan L.; Johnson, Susan L.
Eating-related routines, such as regular mealtimes, can protect against obesity. Little is known about eating-related routines among preschoolers or the factors that shape those routines. Ecocultural Theory and qualitative interviews with 30 caregivers of preschoolers in Colorado were used to describe eating-related routines at home and parents' perspectives on the factors that shape routines. Qualitative content analysis was used to analyze and interpret data. Consistent with clinical recommendations, parents' goals included dinner meals where adults and preschoolers eat the same food, in the same place, at the same time. However, parents' employment schedules and challenges in managing preschoolers' behavior prevented parents from consistently enacting recommended routines. Educating parents alone may not be sufficient to ensure optimal eating-related routines among preschoolers, and the household context needs to be considered. Families organized routines according to cultural values and available resources.